(untitled) (Revista de Investigaciones Universidad del Quindío, 2013)
This article presents the results of photocatalytic degradation of Congo Red (CR), using as catalyst TiO2 in suspension, irradiated by sunlight in a Compound Parabolic Collector (CPC). The optimal operation conditions for CPC were determined in terms of flow and concentration of TiO2, finding that the degradation improves when handling a concentration of 175 mg.L-1 of TiO2, and a flow rate 15.5 Lmin-1. Under these conditions a 100% of RC degradation is reached with a constant kinetic of 0.0228min-1 and 77% of mineralization with a kinetic constant of 0.000223 Lmg-1min-1. The kinetic study was performed for 6h finding, for degradation a pseudo-first order kinetic and for mineralization second order kinetic Also the effect of the concentration of 20, 60 and 100 mgL-1of RC in the solar photocatalytic degradation was evaluated. For this, consider the kinetics of degradation and mineralization byproducts as nitrates and sulfates. For this, it was considered the kinetics of degradation and mineralization of by-products as nitrates and sulfates. For each concentration, it was obtained a pseudo-first-order kinetics, the maximum concentrations of nitrates (4.6, 7.2, and 15.2) mg.L-1, and sulfates (1.8, 2.3, and 2.3) mg.L-1 respectively. A quantitative study was implemented for degradation via HPLC showing a retention time of 1.207min for the RC with a decreasing in the peak intensity over time.